(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2022)
The Covid-19 problem has hastened a pace of significant digitalization in economic production and services that had already begun. For the first time, AI and robotics are becoming autonomous and self-learning, with human-like capabilities. The need to examine digitalization and the future of work has grown even more urgent. Until recently, labour unions were the most powerful institutions representing workers. However, the increasing prospect of intelligent robots replacing humans calls into doubt the viability of labour union policy. This development jeopardises their conventional power bases, which rely on the participation of large numbers of salaried workers and their ability to halt production. This paper tries to analyse the issues that unions face in capitalist democracies in this setting. The premise that the digital revolution will eventually generate new, better jobs has been endorsed by the majority of research work on labour relations. We propose that we investigate an alternate scenario, namely, a digital revolution that results in mass human worker replacement and structural, technological unemployment, which could broaden our perspective, particularly in terms of public policy design. We believe that labour unions now play two critical roles. The first is to protect workers’ rights and interests as the economy shifts from paid labour to automated-autonomous production; and the second is to change their primary mission from representing employees to representing the social rights of all citizens, particularly the material interests of laypeople.